Coronavirus (COVID - 19): Chemical Entities of Biological Interest - Mahajan, Aman; Gupta, Princy (Mini Reviews in Medicinal Chemistry, 2021)
Virus, a sub-microscopic infectious agent that replicates only inside the living cells of a host, causes viral infection. Currently, the immediate imperative is to control the combat against novel coronavirus outbreak caused by the COVID-19 virus, which started in China and spread all over the world. The domain of travelling has emphasized COVID-19 virus prevention as a serious issue for the safety of human beings. The exponential rise in the number of corona patients is a matter of concern for governing bodies of various countries in spite of countless cooperative efforts put in by citizens, organizations and government. India is now among the top worst hit nation in terms of the spread of COVID-19 pandemic. The present article reviews various state-of-art medicinal approaches available that are presently used to control the spread of coronavirus pandemic.
Keywords: Virus